2022
DOI: 10.3389/fbioe.2022.944869
|View full text |Cite
|
Sign up to set email alerts
|

A remineralizing orthodontic etchant that utilizes calcium phosphate ion clusters

Abstract: This study aimed to investigate whether a phosphoric acid (H3PO4) solution containing calcium phosphate ion clusters (CPICs) could minimize enamel damage during long-term bracket bonding by dissolving the enamel surface and promoting enamel remineralization. The experimental design is as follows: first, three experimental etchants (H3PO4, CPICs-incorporated H3PO4 solution-I, and CPICs-incorporated H3PO4 solution-II) and two bonding resins (conventional orthodontic resin and self-adhesive orthodontic resin) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…44 In this study, the EDX analysis data coincided with those of previous studies, which showed that the enamel was mainly composed of Ca and P before and after CPIC treatment. 42,44,45 The improvement in the Ca/P ratio supports the remineralization of demineralized enamel and structural enamel repair using a calcium phosphate solution. Because the Ca/P ratio improved with CPIC application, remineralization of enamel using CPICs is a promising approach for treating the early stages of tooth erosion.…”
mentioning
confidence: 77%
“…44 In this study, the EDX analysis data coincided with those of previous studies, which showed that the enamel was mainly composed of Ca and P before and after CPIC treatment. 42,44,45 The improvement in the Ca/P ratio supports the remineralization of demineralized enamel and structural enamel repair using a calcium phosphate solution. Because the Ca/P ratio improved with CPIC application, remineralization of enamel using CPICs is a promising approach for treating the early stages of tooth erosion.…”
mentioning
confidence: 77%